Defluoridation of drinking water using chemically modified bentonite clay - Kamble, Sanjay P.; Dixit, Priyadarshini; Rayalu, Sadhana S.; Labhsetwar, Nitin K. (Desalination, 2009)
Adsorption potential of metal oxide (lanthanum, magnesium and manganese) incorporated bentonite clay was investigated for defluoridation of drinking water using batch equilibrium experiments to gain insight of adsorption behavior, kinetics and mechanisms of adsorption of fluoride ion. The effect of various physicochemical parameters such as pH, adsorbent dose, initial fluoride concentration and the presence of interfering co-ions on adsorption of fluoride has been investigated. The 10%La-bentonite shows higher fluoride uptake capacity for defluoridation of drinking water as compared to Mg-bentonite, Mn-bentonite and bare bentonite clay. The uptake of fluoride in acidic pH was higher as compared to alkaline pH. The equilibrium adsorption data fitted reasonably well in both Langmuir and Freundlich isotherm models. It was also observed that in the presence of certain co-existing ions can have positive effect on removal of fluoride, while carbonate and bicarbonate anions show deleterious effect. The rate of adsorption was reasonably rapid and maximum fluoride uptake was attained within 30 min. The modified adsorbent material shows better fluoride removal properties for actual field water, which could be due to the positive effect of other co-ions present in the field water. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 10%La-bentonite; Defluoridation; Kinetic modeling; Langmuir and Freundlich adsorption isotherms; Water treatment

Defluoridation of drinking water using pural (R) MG-20 mixed hydroxide adsorbent - Patankar, Gaurang V.; Tambe, Amruta S.; Kulkarni, Bhaskar D.; Malyshew, Alexander; Kamble, Sanjay P. (Water Air and Soil Pollution, 2013)
The potential ofmixed alumina-magnesia hydroxide adsorbent (PURAL (R) MG-20) for defluoridation of drinking water using batch and continuous mode of operations has been reported in the present article. Systematic adsorption experiments were carried out to elucidate the effects of different process parameters such as adsorbent dose, initial fluoride concentration, pH of the solution and effect of other ions (usually present in groundwater). These studies were aimed to understand the adsorption behaviour of the PURAL (R) MG-20 adsorbents. Fluoride adsorption by PURAL (R) MG-20 sorbent was found pH dependent. Maximum fluoride removal efficiency was observed in the range of pH 5-7. Langmuir isotherm described the data better than Freundlich and Temkin isotherm models and the adsorption capacity was found to be 5.62 mg g(-1) at initial fluoride concentration of 5.13 mg L-1, pH 7 and contact time 24 h. The kinetic result shows that the fluoride sorption follows pseudo-second-order kinetics. Column breakthrough studies were performed to test the performance of the adsorbent media at continuous mode of operation. Thus, it can be concluded that PURAL (R) MG-20 adsorbent can be used directly for field applications since it shows high fluoride uptake capacity under simulated drinking water conditions and it is also commercially available.
Keywords: Breakthrough studies; Defluoridation of drinking water; Kinetic modelling; Mixed hydroxide adsorbent